A Comparative Study of Local Dietary Intake Among Subjects with Hypertensive Disorders of Pregnancy Attending Antenatal Care - Chibuike F. Chukwunyere; David O. Awonuga; Taiwo Olunuga; Ifeoma C. Udenze (European Medical Journal Reproductive Health)
Background: Hypertensive disorders of pregnancy remain among the most significant causes of pregnancy-related complications. The research by the Dietary Approaches to Stop Hypertension (DASH) group revealed that non-pharmacological measures and intervention such as diet can be used to control blood pressure. Objective: This study was completed to determine the frequency of consumption of local food among females who were pregnant and their relationship with pregnancy-related hypertensive disorders. Methods: This was a descriptive research study of females who were pregnant with pre-eclampsia (PE) and gestational hypertension (GH) who presented at the Federal Medical Centre (FMC), Abeokuta, Nigeria. During the study period (September–October 2019) at the tertiary healthcare centre, 45 subjects who were pregnant were select from a PE and GH group, and matched with 45 patients with normotension. Comparison of bean meal onsumption (gbegiri) and bone meal (gbure-oloboro) consumption in subjects who were pregnant did not reveal statistically significant differences in those with PE and GH. Results: The findings reveal a statistically significant difference in milk consumption between females who were pregnant with mild and severe PE (p=0.019). There was also a statistically significant difference in subjects with mild and severe GH who consumed milk (p=0.003).